TEACHERS’ PERCEPTION IN USING CALL AND TEACHERS’ HABIT IN TEACHING ENGLISH OF SECONDARY SCHOOL IN JAKARTA - Widi Sriyanto; Lifia Nur Zagita; Martriwati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
This study intended to know the correlation between teachers’ ability on using CALL and their habit in teaching secondary school in Jakarta. The independent variable (X) is the teachers’ perception in using CALL; meanwhile, the dependent variable (Y) is teachers’ habit in teaching. The research used quantitative method that applied questionnaire as the instrument to collect the data. The population in this research was 100 teachers, but the writers only took 80 teachers as the sample of this research. The writers used random sampling technique. To obtain the data of X variable (teachers’ perception in using CALL) and Y variable (teachers’ habit in teaching), the witers distributed quistionnaire consisted of 40 items. The writers used Pearson Product Moment’s formula to calculate the correlation between X variable and Y variable. After analyzing the data, it was found that both sample data (X and Y) were normally distributed because χ2o < χ2t X data (3.91 < 9.49), and Y data (8.13 < 9.49). The correlation was found r-observed = 0.333 and r-table = 0.217 in a significant 0.05 with n = 80. Because r-observed < r-table, Ho was rejected and HI was accepted. It means that there was a significant relationship between teachers’ habit in teaching English with technology and their competency in using CALL.